Integrating ecosystem health diagnosis into the construction of ecological security network—A case study in Qujing City, China. (February 2023) - Chen, Yan; Ma, Yuewei; Pan, Jianfeng; Zhang, Shenglan; Zhang, Xuyang; Wu, Rui; Li, Xiaoyan
Highlights: Ecological security were assessed by building ecosystem health framework. Ecosystem health index were used to identify ecological source. Ecological corridors, nodes and barrier were identified using circuit theory. Abstract: With the rapid development of the social economy, habitat fragmentation is becoming more and more obvious, which seriously threatens regional ecological security and sustainable development. Understanding the ecological health status of mountainous cities is of great significance for improving the efficiency of ecological protection. However, the research on the ecosystem health and ecological network construction of mountain cities is still limited. Given the shortcomings of the research, this study constructed an ecosystem health assessment framework in Qujing City, identifying ecological sources with the help of health diagnosis results, simulating biological walking paths with circuit theory, and identifying ecological "nodes" and barrier points. The results showed that: (1) From 2000 to 2020, the ecosystem health level of Qujing City increased first and then decreased. The ecological risk spillover phenomenon existed in the urban center area, which was strongly affected by human activities. (2) Based on VORE model and landscape connectivity software consensus, 27 ecological sources were mainly composed of forest and grassland, and the total area was 7068.24 km 2 . (3) 53 ecological corridors were identified by the circuit theory, with a length of 734.33 km, 83 ecological sandwichs, a total area of 58.59 km 2, and 49 ecological barrier points, among which the ecological sandwichs mostly coincided with the river corridor. The barrier points were concentrated in the north and southeast of the study area. This study can provide a scientific reference for the ecological restoration of mountainous cities.